Application of Ni - W Alloy Plating on Drilling Tool Thread Surface - LU Xi - ning, DING Jie - qiong, YU Shi - jie (Cailiao Baohu, 2021)
The failure of drilling tool joint mostly occurs on the surface of thread. Copper plating and phosphating treatment can effectively relieve thread sticking, but the pollution of copper plating and phosphating process is serious, for this, Ni - W alloy coating on thread surface of drilling tool joint was prepared and the effect of Ni - W alloy plating on the thread performance of drilling tools was studied. Experimental results showed that the thickness of Ni - W alloy coating was 10～60 μm. The microhardness of Ni - W alloy coating was 700～900 HV1 N, which was 2～3 times of that of the substrate materials. The thickness of the Ni - W alloy coating was uneven and decreased successively on the top, side and bottom surfaces of the thread teeth , which had an adverse effect on the meshing degree of thread teeth during working. Ni - W alloy coating joint was damaged in the first 3 make - up and break - down tests. Fatigue life test showed that the fatigue life of Ni - W alloy coating samples was about 20% of the samples without coatings. It was believed that the amorphous structure of the Ni - W alloy coating that significantly increased the hardness of coating, but reduced the plastic deformation ability and fatigue performance of the material. Besides, the uneven thickness of the coating led to serious sticking of the joint.